Trade union priority list for REACH Authorisation. Version 2.0 - Santos, Tatiana; Romano, Dolores; Gadea, Rafael; Musu, Tony (Brussels, 2010)
"The version 2.0 includes 334 substances or group of substances ordered by priority, this represents 29 new entries compared to the first version published in March 2009. The trade union organisation wants a maximum of them requiring authorisation under REACH. "